Guarding the guards: education, corruption, and Nepal’s commission for the investigation of abuse of authority (CIAA) - Gellner, D; Adhikari, K (Brill, 2020)
With development, democratization, and market reforms, corruption has become pervasive in Nepal, especially in areas where government licencing is required. Medical education is a site of considerable political and public contention, because of the nexus that links politicians, educational entrepreneurs, and the licencing of medical colleges. The case of Lokman Singh Karki, the notorious chief of the Commission for the Investigation of Abuse of Authority (ciaa) from 2013 to 2016 is explored, as is that of his nemesis, the campaigner for the reform of medical education, Dr Govinda KC. The ciaa was for a time converted into a prime instrument of corruption instead of being a defence against it. Different scales of reciprocity and differing moral valuations of reciprocity lie at the heart of the fierce moral debates over the rightness or wrongness of Dr KC’s hunger strikes.